Variations on a Theme - Ramirez, Bruno (Labour / Le Travail, 2000)
Discusses the film, "La Sarrasine" (1992), a drama about an Italian immigrant couple in Quebec that is confronted with tragedy. The author, a historian, co-wrote the screenplay with the director, Paul Tana.